Políticas Públicas en educación y su incidencia en el crecimiento económico periodo 2007 - 2021 - Pallchisaca Loja, Elsa Yolanda (2023)
ABSTRACT: This study investigated the impact of education policies on Ecuador’s economic growth between 2007 and 2021. Key educational variables were identified and analyzed how these policies influenced the country’s economy. Policies promoting universal access and academic quality, modernization of the education system, and poverty reduction quality modernization of education system and poverty reduction were highlighted as critical factors for economic development. A sound methodological approach was used, and external factors such as financial crises and the COVID-19 pandemic were considered. The results highlighted the importance of education policies in economic growth and made recommendations for future research and policy formulation.